2020
DOI: 10.1016/j.cmi.2020.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen use and clinical outcomes in COVID-19 patients

Abstract: Objective: It was recently suggested that ibuprofen might increase the risk for severe and fatal coronavirus disease 2019 and should therefore be avoided in this patient population. We aimed to evaluate whether ibuprofen use in individuals with COVID-19 was associated with more severe disease, compared with individuals using paracetamol or no antipyretics. Methods: In a retrospective cohort study of patients with COVID-19 from Shamir Medical Centre, Israel, we monitored any use of ibuprofen from a week before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
2
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(135 citation statements)
references
References 6 publications
6
116
2
11
Order By: Relevance
“…Therefore, the findings of these studies may not be applicable to COVID-19. However, very recently Rinott et al [21] published a retrospective cohort study of 403 cases of COVID-19 patients, recruiting those who used "any medication containing ibuprofen, paracetamol or dipyrone starting a week before diagnosis of COVID-19". Their conclusions therefore address the issue of acute use of NSAIDs and found no significant association between ibuprofen usage and clinical outcomes (including mortality) when comparing the NSAID group with cohorts using paracetamol or no antipyretic.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the findings of these studies may not be applicable to COVID-19. However, very recently Rinott et al [21] published a retrospective cohort study of 403 cases of COVID-19 patients, recruiting those who used "any medication containing ibuprofen, paracetamol or dipyrone starting a week before diagnosis of COVID-19". Their conclusions therefore address the issue of acute use of NSAIDs and found no significant association between ibuprofen usage and clinical outcomes (including mortality) when comparing the NSAID group with cohorts using paracetamol or no antipyretic.…”
Section: Discussionmentioning
confidence: 99%
“…However, this statement, although it contributes to the described use of NSAIDs for the empirical treatment and prevention of COVID-19 [93], requires its experimental demonstration because our predictions cannot guarantee a pharmacologically and clinically relevant interaction. Therefore, more studies are needed, especially given the real controversy that exists regarding the use of these drugs against COVID-19 [19][20][21][22][23][24][25][26][27]. Especially because to date, only one theoretical report of a binding of ligand at the interface of the RBD-ACE2 complex is known [49,50], but this binding is in a different region than the one found in this work, in our work the binding of Ibuprofen occurs in an allosteric region.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the use of NSAIDs such as Ibuprofen is highly controversial because it has been reported that in animal models it can mediate the overexpression of the angiotensinconverting enzyme 2 (ACE2) essential for viral recognition and it has been speculated that this could increase the risk of COVID-19 [19][20][21][22][23]. However, in various investigations in patients with COVID-19, the use of Ibuprofen has not been associated with worse clinical outcomes, compared to other NSAIDs such as Acetaminophen [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have also criticized the theoretical basis upon which ibuprofen was avoided in COVID-19 [ 40 , 41 ] and the claims against other drugs mentioned with ibuprofen in that contradictory hypothesis are similarly being revoked [ 42 ]. Notably, ibuprofen has been previously hypothesized to be hazardous in another medical argument and later on that hypothesis was proven incorrect [ 43 ] and recently a clinical study has shown that ibuprofen use was not associated with worse clinical outcomes, compared with paracetamol or no antipyretic [ 44 ]. Similarly, Use of NSAIDs was not associated with 30-day mortality, hospitalization or complications in Danish individuals who tested positive for SARS-CoV-2 [ 45 ].…”
Section: Ibuprofen Is Currently Being Proven To Be Beneficial For Covmentioning
confidence: 99%